Sistema de información para la gestión de eventos, recursos y traslados en las ambulancias de la Cruz Roja Colombiana Seccional Cundinamarca Bogotá (2021)
In the Colombian Red Cross Sectional Cundinamarca Bogotá the Extra Mural process performs the management of ambulance transfers, from a SAMU or IPS to the place authorized by the healthcare provider of the patient who needs this service